N-doped porous carbon supported Ni catalysts derived from modified Ni-MOF-74 for highly effective and selective catalytic hydrodechlorination of 1, 2-dichloroethane to ethylene. (February 2020) - Ning, Xin; Sun, Yuhan; Fu, Heyun; Qu, Xiaolei; Xu, Zhaoyi; Zheng, Shourong
Abstract: Metal-organic frameworks (MOFs) have received significant attention as promising precursors or sacrificial templates in the preparation of porous carbon supported catalysts. In this study, N-doped porous carbon supported Ni catalysts (denoted as Ni/NC) were prepared using furfuryl alcohol (FA) loaded Ni-MOF-74 as the precursor followed by NH4 OH treatment and pyrolysis under N2 atmosphere. For comparison purpose, Ni catalysts supported on porous carbon (denoted as Ni/C) were also prepared by direct pyrolysis of Ni-MOF-74. The selective gas phase catalytic hydrodechlorination of 1, 2-dichloroethane to ethylene was carried out to evaluate the catalytic performances of the catalysts. It was found that for Ni catalysts prepared at the same pyrolysis temperature, Ni particle sizes in Ni/NC catalysts were significantly smaller (20–40% smaller) than that of Ni/C. This reflected that pre-modification of Ni-MOF-74 using FA and NH4 OH could effectively increase Ni dispersion in Ni catalysts derived from Ni-MOF-74. Moreover, Ni/NC had a markedly stronger ability to form spillover H2 owing to the enhanced metal-support interactions by N-doping. Accordingly, Ni/NC catalysts exhibited much higher catalytic activities than Ni/C catalysts. The turnover frequencies of Ni/NC catalysts were found to be 1.22–1.65 times higher than Ni/C catalysts. Increasing pyrolysis temperature led to decreased catalytic activities of both Ni/C and Ni/NC catalysts, due to the aggregation of Ni particles at higher treatment temperature. The findings from this study demonstrate that the MOF-mediated synthesis method offers a promising way to prepare Ni-based catalysts for catalytic hydrodechlorination of chlorinated hydrocarbons. Graphical abstract: Image 1 Highlights: N-doped carbon supported Ni (Ni/NC) was prepared by facile pyrolysis of modified MOF. N-doping increased Ni dispersion and enhanced metal-support interaction in Ni/NC. Ni/NC was used for selective hydrodechlorination of 1, 2-dichloroethane to ethylene. Ni/NC had high catalytic activity, stability and selectivity for hydrodechlorination.